2011
DOI: 10.52283/nswrca.ajbmr.20110102a06
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personality and Leadership Styles on Leading Change Capability of Malaysian Managers

Abstract: This study was conducted to investigate the influence of the Big Five Dimensions of personality of the Malaysian Managers and the leadership styles these managers use on their leading change capabilities. Total sample of 105 managers was used in this study. The results of this study revealed that the Malaysian managers tend to enjoy personalities that are conscious and open to experience. These managers tend to use consultative leadership style. However, they use autocratic, democratic and some of them use lai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…The leaders preferring an autocratic leadership style could have high imaginative influence, curiousness, and frequent change in ideas due to open-mindedness. Therefore, this leadership style sometime might be associated with openness to experience (Alkahtani et al, 2011). The other part of the hypothesis is consisting of the research findings conducted by Hildenbrand et.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The leaders preferring an autocratic leadership style could have high imaginative influence, curiousness, and frequent change in ideas due to open-mindedness. Therefore, this leadership style sometime might be associated with openness to experience (Alkahtani et al, 2011). The other part of the hypothesis is consisting of the research findings conducted by Hildenbrand et.…”
Section: Discussionmentioning
confidence: 96%
“…The existing findings coincided with and were validated by organizational-based research surveys to find the connection between personality traits and preferred leadership styles. The findings of these researches revealed that personality traits were significantly associated with preferred leadership styles (Breevaart & de Vries, 2017;De Vries, 2012;Alkahtani et al, 2011;Moss & Ngu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The primary idea behind this leadership style is that leaders are skilled professionals who control and monitor their subordinates. Alkahtani et al (2011) define followers (employees) as obedient subordinates who obey directions. Autocratic leaders in companies, according to Balunywa (2000), are more concerned with despotic influence to get the work done than with the development and growth of subordinates.…”
Section: Autocratic Leadershipmentioning
confidence: 99%
“…In a multi-racial nation such as Malaysia, it would be interesting to identify the nature of using cultural intelligence as there are major differences in the socio-cultural backgrounds among various ethnic groups [8,9]. Alkahtani et al [10] found that there were different research results with respect to expatriate leadership style in Malaysia. For example, Malaysian leaders are found not so much of designating but rather more valueoriented.…”
Section: Introductionmentioning
confidence: 99%